Evaluasi Risiko yang Harus Dihadapi Vendor dalam Memenuhi Kebutuhan Permintaan Produk Perishable Bencana Gunung Api Menggunakan Simulasi Monte Carlo - Prasetyo, Ikhsan; Cakravastia, Andi (Journal of Research in Industrial Engineering and Management, 2024)
As a nation situated within the Pacific Ring of Fire, Indonesia is home to numerous volcanoes. Of the many active volcanoes present, approximately 40% are inadequately monitored. This situation positions Indonesia as one of the countries facing a significant threat from volcanic disasters. One of the critical challenges in disaster management lies in the logistics of disaster relief, particularly in managing perishable food supplies to meet the needs of affected victims. The handling of such logistical items must ensure that no expired products are utilized. One approach to addressing this challenge is to delegate management authority to third parties, specifically vendors who also handle daily demands. This strategy is intended to allow perishable products to be managed through rotation to fulfill all requests while vendors maintain vigilant oversight of existing inventory levels in warehouses. This research aims to evaluate the risks that a vendor must confront when implementing such a collaborative arrangement. The evaluation is conducted using Monte Carlo simulation to determine the optimal scenario that vendors can select. Analysis results indicate that the implementation of Scenario 2, which assumes that a disaster may occur once throughout the planning period, represents the most favorable scenario for vendors. The study underscores the importance of proactive disaster preparedness and efficient resource management in a country prone to volcanic activity. By exploring innovative approaches to logistics and inventory control, stakeholders can enhance their capacity to respond effectively to potential disasters, ultimately contributing to improved disaster resilience in Indonesia.